The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5194/isprs-archives-xlii-2-1183-2018
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and 3d Cultural Heritage Documentation Using a Modified Camera

Abstract: ABSTRACT:Spectral and 3D imaging techniques are used for museum imaging and cultural heritage documentation providing complementary information to aid in documenting the condition, informing the care, and increasing our understanding of objects. Specialised devices for spectral and 3D imaging may not be accessible for many heritage institutions, due to cost and complexity, and the modification of a consumer digital camera presents the potential of an accessible scientific tool for 2D and 3D spectral imaging. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Although, recently, simple to use automated or semi-automated photogrammetric software implementing Structure from Motion (SfM) and Multiview Stereo (MVS) algorithms, which are becoming extremely popular for heritage applications, in combination with low-cost sensors, have made heritage digitization more feasible (Georgopoulos and Stathopoulou, 2017). More specifically, the availability of low-cost digital and modified digital cameras for UVA, IRA and multi-spectral imaging, that are not any more restricted to very low resolutions has made possible the direct modeling from non-VIS imagery (Grifoni et al, 2018;Webb et al, 2018). It should also be mentioned that many contemporary mobile phone cameras can produce imagery of adequate quality for photogrammetric use and have already successfully been implemented in case studies for rapid cultural heritage mapping (Calantropio et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although, recently, simple to use automated or semi-automated photogrammetric software implementing Structure from Motion (SfM) and Multiview Stereo (MVS) algorithms, which are becoming extremely popular for heritage applications, in combination with low-cost sensors, have made heritage digitization more feasible (Georgopoulos and Stathopoulou, 2017). More specifically, the availability of low-cost digital and modified digital cameras for UVA, IRA and multi-spectral imaging, that are not any more restricted to very low resolutions has made possible the direct modeling from non-VIS imagery (Grifoni et al, 2018;Webb et al, 2018). It should also be mentioned that many contemporary mobile phone cameras can produce imagery of adequate quality for photogrammetric use and have already successfully been implemented in case studies for rapid cultural heritage mapping (Calantropio et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The availability of high-resolution, easily operated digital cameras for NIR acquisition, in combination with SfM/MVS image-based modeling techniques, has made feasible the 3D spectral modeling for heritage applications. Contemporary research, which showed promising results [22][23][24][25][26][27][28], led us to the motivation for further experimentation.…”
Section: Near-infrared Imaging and Modelingmentioning
confidence: 99%
“…The availability of high-resolution easily operated digital cameras for NIR acquisition, in combination with SfM/MVS image-based modeling techniques, has made feasible the 3D spectral modeling for heritage applications. Contemporary research which showed promising results [29][30][31][32] led us to the motivation for further experimentation.…”
Section: Near-infrared Imaging and Modelingmentioning
confidence: 99%